LncRNAs GACAT3 and LINC00152 regulate each other through miR‐103 and are associated with clinicopathological characteristics in colorectal cancer. Issue 9 (27th May 2020) - Ye, Shazhou; Lu, Yicong; Ru, Yuqing; Wu, Xiaoyue; Zhao, Ming; Chen, Jiayi; Xu, Mingjun; Huang, Qin; Wang, Yibo; Shi, Shanping; Bu, Shizhong; Xi, Yang
Abstract: Background: Long non‐coding RNAs (lncRNAs) perform pivotal regulatory roles in tumor development. Our previous work revealed that the lncRNA gastric cancer‐associated transcript 3 ( GACAT3 ) was significantly overexpressed and associated with tumor size and metastasis in gastric cancer. Methods: Total RNAs were extracted from colorectal cancer (CRC) and reverse transcribed, and then quantitative real‐time PCR (qRT‐PCR) was conducted. Cell counting was performed to assess the effect of GACAT3 on CRC cell line proliferation. Bioinformatics prediction, dual luciferase assay, miRNA mimics, siRNAs, and transfection experiments were applied to determine whether GACAT3 and LINC00152 are reciprocally regulated by miR‐103. The relationship between their expression levels and clinicopathological factors of patients was explored. A receiver operating characteristic (ROC) curve was used to assess the potential diagnostic value of GACAT3 and LINC00152 . Results: GACAT3 was identified to be highly expressed in CRC tissues and associated with cell proliferation. Furthermore, we demonstrated that GACAT3 acted as a competing endogenous RNA of LINC00152 and they were both regulated by miR‐103. Moreover, analysis of clinicopathological characteristics revealed that GACAT3 and LINC00152 were positively correlated with the depth of invasion, TNM stage, lymph node metastasis, and CA19‐9 level. Importantly, a combination of GACAT3 and LINC00152 showed a superior diagnostic capacity compared with the use of the two molecules alone. Conclusion: Our work shows that GACAT3 and LINC00152 are both overexpressed in CRC and they act as a ceRNA network. Therefore, our data suggest that GACAT3 and LINC00152 may be a promising potential diagnostic biomarker for CRC.